2019
DOI: 10.1098/rsos.180748
|View full text |Cite
|
Sign up to set email alerts
|

Public questions spur the discovery of new bacterial species associated with lignin bioconversion of industrial waste

Abstract: A citizen science project found that the greenhouse camel cricket ( Diestrammena asynamora ) is common in North American homes. Public response was to wonder ‘what good are they anyway?’ and ecology and evolution guided the search for potential benefit. We predicted that camel crickets and similar household species would likely host bacteria with the ability to degrade recalcitrant carbon compounds. Lignocellulose is particularly relevant as it is difficult to degrade yet is an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 65 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…Bacillus altitudinis RSP75 also showed a growth pattern similar to B. megaterium S3, showing slow and extended growth on CMC media [68] due to a metabolic shift to use cellulose as a carbon source. One of the peculiarities of B. altitudinis RSP75 is the ability to grow under acidic pH because relatively few bacterial species are known to tolerate acidic conditions, particularly in nature [69]. The acidophilic nature of B. altitudinis RSP75 signifies that its enzymes are likely to function well at acidic pHs prevailing in biomass conversion processes.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus altitudinis RSP75 also showed a growth pattern similar to B. megaterium S3, showing slow and extended growth on CMC media [68] due to a metabolic shift to use cellulose as a carbon source. One of the peculiarities of B. altitudinis RSP75 is the ability to grow under acidic pH because relatively few bacterial species are known to tolerate acidic conditions, particularly in nature [69]. The acidophilic nature of B. altitudinis RSP75 signifies that its enzymes are likely to function well at acidic pHs prevailing in biomass conversion processes.…”
Section: Discussionmentioning
confidence: 99%
“…The conversion of lignin in anaerobic systems remains an enigma, as it is believed that oxygen is necessary for this process to occur. Studies have been dedicated to the chemical process of lignin conversion and determining which microorganisms are capable of carrying out this process [117][118][119]. Geib and collaborators [120] found out that lignin degradation can also occur in a different ecosystem, in the gut of wood-feeding insects, and that it is not restricted to wood-rot fungal systems.…”
Section: Bacterial Community Structurementioning
confidence: 99%
“…Geib and collaborators [120] found out that lignin degradation can also occur in a different ecosystem, in the gut of wood-feeding insects, and that it is not restricted to wood-rot fungal systems. Bacteria capable of growing on lignin and on a waste product from the paper industry (black liquor) were isolated from the greenhouse insect camel cricket (Diestrammena asynamora) and hide beetle (Dermestes maculatus) [118]. Studies carried out by Scully and collaborators revealed that the Asian long-horned beetle (Anoplophora glabripennis), a wood-feeding insect, harbors complex microbiota capable of degrading hemicellulose, enhancing the degradation of lignin, and fermenting xylose [121,122].…”
Section: Bacterial Community Structurementioning
confidence: 99%
“…The laccase activity was detected in the lignin medium at pH 6–8 inoculated by C. lapagei , while superoxide dismutase, glutathione S-transferase, alkyl hydroperoxide reductase and glutathione reductase were found on the cellulose or hemicellulose containing medium. Additionally, the study found other enzymes related to lignin and carbohydrate degradation, which could play a vital role in industrial processes [ 64 ].
Fig.
…”
Section: Biological Pretreatmentmentioning
confidence: 99%